ROLE OF TECHNOLOGY IN LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The word “technology”  is  not  only  used  in  industry, but  also  is  used  in  educational  system. Simply said, technique  means to modernize and develop and  this branch by using new teaching strategies, new methods.